Evaluation of Oral Health Practitioners and Facilities on Preparedness for Medical emergencies in Dental practices, Ndola – Zambia: A pilot study - Majamabo et al. (Rwanda Medical Journal)
INTRODUCTION: Preparedness to handle medical emergencies in dental practices depends on a range of factors, such as understanding the magnitude of the problem, availability of essential medical emergency drugs and equipment, and trained personnel. This pilot study aimed to inventory these factors in the available oral health facilities in Ndola, Zambia, to establish the preparedness level for handling these emergencies.